Serum inflammatory markers in relation to prostate cancer severity and death in the Swedish AMORIS study. Issue 11 (26th January 2018) - Arthur, R.; Williams, R.; Garmo, H.; Holmberg, L.; Stattin, P.; Malmström, H.; Lambe, M.; Hammar, N.; Walldius, G.; Robinsson, D.; Jungner, I.; Van Hemelrijck, M.
Abstract : Inflammation is a well‐documented driver of cancer development and progression. However, little is known about its role in prostate carcinogenesis. Thus, we examined the association of C‐reactive protein (CRP), haptoglobin, albumin and white blood cells (WBC) with prostate cancer (PCa) severity (defined by PCa risk category and clinicopathological characteristics) and progression (defined by PCa death). We selected 8, 471 Swedish men with newly diagnosed PCa who had exposure measurements taken approximately 14 years prior to diagnosis. We calculated odds ratio (OR) and 95% confidence interval (CI) for the associations between the inflammatory markers and PCa severity using logistic regression, while Cox proportional hazard regression was used for the associations with overall and PCa death. Serum CRP levels were associated with increased odds of high risk and metastatic PCa, and high PSA levels (≥20 µg/L) (OR: 1.29; 95% CI: 1.06–1.56, 1.32; 1.05–1.65 and 1.51; 1.26–1.81, respectively). Similarly, higher haptoglobin levels were associated with increased odds of metastatic PCa, high PSA level and possibly high grade PCa (1.38; 1.10–1.74, 1.50; 1.17–1.93 and 1.25; 1.00–1.56, respectively). Albumin was positively associated with Gleason 4 + 3 tumour (1.38; 1.02–1.86) and overall death (HRunit increase in log : 1.60; 95% CI: 1.11–2.30), but inversely associated with high risk PCa and high PSA levels (≥20 µg/L) (0.71; 0.56–0.89 and 0.72; 0.5 9–0.90). WBC was associated with increased odds of T3–T4 PCa. Except for albumin, none of these markers were associated with PCa death or overall death. Systemic inflammation as early as 14 years prior to diagnosis may influence prostate cancer severity. Abstract : What's new? High levels of C‐reactive protein can presage a particularly malignant prostate cancer, new results show. Cancers certainly arise in the wake of chronic inflammation, but it's not known exactly how markers of inflammation initiate prostate cancer. Here, the authors show that systemic inflammation can worsen the severity of the cancer, even if it occurred long before the cancer's onset. High levels of CRP and haptoglobin, they found, were associated with prostate cancer with high PSA and metastasis. The question remains whether inflammation pushes cancer cells into a more malignant mode, or selects for the more dangerous cells early on.